Chemotherapy in Lung Cancer With Hepatic and Renal Impairment - Aida Hastuti; Erna Kusumawardhani; Haryati Haryati (Respiratory Science, 2022)
Chemotherapy is one of the therapeutic modalities for lung cancer. Chemotherapy with anticancer drugs has a narrow therapeutic index and pharmacokinetic variability between individuals. The administration of anticancer drugs should consider many factors that may affect the pharmacokinetics of the drug, such as hepatic and renal function. In lung cancer patients who have hepatic and renal impairment, an adjusted dose of anticancer drug is needed to achieve levels of drug exposure similar to patients who have normal organ function and avoid toxicity. Renal function is calculated by the glomerular filtration rate or creatinine clearance. Assessment of hepatic function can be taken from Child Pugh's score or from bilirubin and aminotransferase enzyme data in patients. In addition, hepatitis screening is also required. The results of the assessment will determine the adjustment dose recommendation for anticancer drugs.